1989
DOI: 10.1042/bj2610233
|View full text |Cite
|
Sign up to set email alerts
|

d-aspartate oxidase in rat, bovine and sheep kidney cortex is localized in peroxisomes

Abstract: D-Aspartate oxidase (EC 1.4.3.1) was assayed in subcellular fractions and in highly purified peroxisomes from rat, bovine and sheep kidney cortex as well as from rat liver. During all steps of subcellular-fractionation procedures, D-aspartate oxidase co-fractionated with peroxisomal marker enzymes. In highly purified preparations of peroxisomes, the enrichment of D-aspartate oxidase activity over the homogenate is about 32-fold, being comparable with that of the peroxisomal marker enzymes catalase and D-amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 31 publications
3
21
0
Order By: Relevance
“…In an earlier biochemical study (Zaar et al 1989), we demonstrated that, in all steps of a subcellular fractionation procedure for kidney cortex homogenates, D-ASPOX activity co-fractionates with peroxisomal marker enzymes. Specific D-ASPOX activity in different species was highest in a peroxisome fraction purified from bovine kidney cortex.…”
Section: Immunoblot Analysis Of Bovine Renal D-aspoxmentioning
confidence: 73%
See 4 more Smart Citations
“…In an earlier biochemical study (Zaar et al 1989), we demonstrated that, in all steps of a subcellular fractionation procedure for kidney cortex homogenates, D-ASPOX activity co-fractionates with peroxisomal marker enzymes. Specific D-ASPOX activity in different species was highest in a peroxisome fraction purified from bovine kidney cortex.…”
Section: Immunoblot Analysis Of Bovine Renal D-aspoxmentioning
confidence: 73%
“…Using highly purified peroxisome preparations from beef, sheep, and rat kidney cortex, as well as rat liver, we demonstrated first that D-ASPOX in these tissues is a peroxisomal enzyme located in the matrix of peroxisomes (Zaar et al, 1989). This peroxisomal localization was later confirmed in isolated organelle fractions from rat and human liver by Van Veldhoven et al (1991).…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations